Retrograde ureteric stent insertion from percutaneous suprapubic access to the bladder in renal transplant recipients with ureteric stenosis: a novel minimally invasive technique - Jian-Hui Wu (BMC Urology, 2020)
Abstract Background Ureteric stricture is a common and salvaging complications after renal transplantation. Two treatment methods are usually used, retrograde ureteral stent placement and percutaneous nephrostomy. The former has a higher failure rate, the latter has a great risk. Therefore, a safe and reliable treatment is needed. Case presentation A technique of retrograde insertion of ureteral stent was established, which was applicable in three transplant recipients with post-transplant ureteral stenosis, and the data was retrospectively recorded. The patients are 2 men and 1 woman, ages 44, 27 and 32 years. These patients underwent a total of five times of retrograde insertion of ureteral stent between 2018 and 2019. None of these patients had any postoperative complication, but all patients had complete recovery from oliguric status within two weeks. Conclusions The retrograde ureteric stent insertion by percutaneous suprapubic access to the bladder (RUS-PSAB) was demonstrated feasibility and safety in a case series with short-term follow-up. However, larger prospective studies are needed.